Improvement of hydrophilicity of polyamide using atmospheric pressure plasma jet - Baniya, H B; Guragain, R P; Baniya, B; Qin, G; Subedi, D P (BIBECHANA, 2020)
Atmospheric Pressure Plasma Jet (APPJ) has many applications in material processing such as surface modification and biomedical material processing. APPJ has been generated by a high voltage power supply (0-20 KV) at an operating frequency of (20-30) 23 kHz. This paper reports the generation and characterization of APPJ in Argon environment and its application in the surface modification of polymeric materials. The discharge has been characterized by optical and electrical methods. In order to characterize the plasma jet, its electron temperature and electron density has been determined by optical emissions spectroscopy. The surface properties of the untreated and plasma treated Polyamide (PA) samples were characterized by contact angle measurement and surface energy analysis. BIBECHANA 17 (2020) 133-138